The star excursion balance test is a reliable and valid outcome measure for patients with knee osteoarthritis. Issue 4 (April 2019) - Kanko, L.E.; Birmingham, T.B.; Bryant, D.M.; Gillanders, K.; Lemmon, K.; Chan, R.; Postic, M.; Giffin, J.R.
Summary: Objectives: Despite the recognized importance of neuromuscular exercises, there is currently no widely accepted clinical outcome measure focused on neuromuscular control for patients with knee osteoarthritis (OA). The purposes of the present study were to investigate the test-retest reliability, concurrent validity and longitudinal validity of the star excursion balance test (SEBT) in patients with knee OA. Design: 74 patients performed the SEBT on two sessions within 7 days, and on a third session after completing 12 weeks of a home exercise program focused on neuromuscular control. A subgroup of 37 performed the SEBT while in the field of view of a motion capture system to estimate concurrent validity. The SEBT was recorded in cm and also normalized to leg length (LL). Participants also completed the 40 m fast-paced walk test and patient-reported outcomes before and after the exercise program. Results: Intraclass correlation coefficients (95% confidence intervals) were 0.94 (0.91 to 0.96) and 0.93 (0.89 to 0.96) and standard errors of measurement were ±2.68 cm and ±3.05%LL for raw and normalized composite scores, respectively. The minimum detectable change at the 95% confidence level for the composite score was 7.44 cm and 8.45%LL. Correlations between observer and motion capture measures were very high (Pearson r  > 0.96). There was a significant increase in SEBT following the exercise program (standardized response mean = 0.74). The change in SEBT had low correlations with changes in 40 m walk times ( r  = 0.26) and pain ( r  = 0.28). Conclusion: The SEBT has suitable measurement properties for use in patients with knee OA.